2015
DOI: 10.4103/1119-3077.153246
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and outcome of postneonatal pediatric emergencies in Nnamdi Azikiwe University Teaching Hospital, Nnewi, South East Nigeria

Abstract: Infectious diseases remain a menace in our environment with the eventual outcome worsened by late presentation to an appropriate health facility. There is an urgent need to create public awareness on the need to seek prompt medical attention for sick children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 9 publications
(21 reference statements)
5
12
3
Order By: Relevance
“…In our series, more than 70% of children with emergency signs are under five with an average age of 2.1 years. Our observation corroborates with those of Ndukwu [4], Fatou [11], Dan [5] and Atanda [6]. This result is explained by the vulnerability of this age group and its susceptibility to several pathologies that weaken its immune status.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our series, more than 70% of children with emergency signs are under five with an average age of 2.1 years. Our observation corroborates with those of Ndukwu [4], Fatou [11], Dan [5] and Atanda [6]. This result is explained by the vulnerability of this age group and its susceptibility to several pathologies that weaken its immune status.…”
Section: Discussionsupporting
confidence: 92%
“…Many child deaths in hospitals occur within 24 hours of admission, whereas they could be avoided if very sick children are identified shortly after arrival and treatment is initiated immediately [1] [4]. These deaths are caused by conditions that are immediately life-threatening.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Australasian authors found that children of 0-4 years of age represented the greatest absolute number of ED presentations in a mixed ED, consistently over time and across all triage categories [9]. In an Indian hospital, subjects 0-5 years of age constituted 78.8% of the study population [3]. Among all children who presented to the ED with face lacerations, not surprisingly, preschool-aged children predominated by far among the study population (34.9% of all study subjects including adults) [10].…”
Section: Age and Gendermentioning
confidence: 91%
“…In comparison to other countries, there is paucity of Swiss data in the published literature on the distribution of presenting medical and surgical complaints in children who visit a paediatric, adult or mixed ED [1][2][3][4][5]. Authors from an English institution have found that breathing difficulty (20.1%), febrile illness (14.1%) and diarrhoea with or without vomiting (14.0%), rash (8.6%) and cough (6.7%) make up most of the medical problems among children aged 1 to 16 years presenting to the PED [1].…”
Section: Introductionmentioning
confidence: 99%
“…3 The significantly worse outcome seen in those with longer duration of illness has been documented in other studies. 12,17,18 This is expected because the longer lasting a diarrhoea episode is, and the longer it takes before effective and appropriate care is sought for a child with diarrhoeal disease, the more likely it is for serious and unsalvageable physiologic aberrations to set in. The poor clinical state at presentation of a significant percentage of the children in our study could be an indirect reflection of the health seeking attitude and literacy level of the population studied.…”
Section: Discussionmentioning
confidence: 99%